If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10y + -64 = -6y Reorder the terms: -64 + -10y = -6y Solving -64 + -10y = -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. -64 + -10y + 6y = -6y + 6y Combine like terms: -10y + 6y = -4y -64 + -4y = -6y + 6y Combine like terms: -6y + 6y = 0 -64 + -4y = 0 Add '64' to each side of the equation. -64 + 64 + -4y = 0 + 64 Combine like terms: -64 + 64 = 0 0 + -4y = 0 + 64 -4y = 0 + 64 Combine like terms: 0 + 64 = 64 -4y = 64 Divide each side by '-4'. y = -16 Simplifying y = -16
| (9)2k=(35)k | | 2x-3x*x=4x+2 | | 0.24(18)+0.04x=0.08(24+x) | | 4y(y^2-y)+(2y+1)(2-1)= | | 3(a+7)=10[a-(4-a)] | | 2z+6+11z-6=180 | | 32=-1.6d | | 2z+6+11z-6=90 | | 32=-1.6(20)+32 | | 32=-1.6d+32 | | 9y+2+3y-8=90 | | 3y-8=9y+2 | | 6X-5((X+2)-2)=8 | | w=32+-1.6d | | w=-1.6d+32 | | 9y+2=3y-8 | | 6X-5((X+2)-2)=12 | | 6X-5((X+2)-2)=1O | | 2x^2-6+5=0 | | 6X-5((X+2)-2)= | | x^2-5y^2+1=0 | | 0=-1.75d+25 | | -25=-1.75d | | 6X-5(X-2)= | | 93.2x=25x+15 | | 6-8x=117-29x | | 6-8x=177-29x | | 5w^2-20w=0 | | 1500=1.80x+120 | | x*5+20= | | 1110=1.25x+110 | | 154-7x=29x+18 |